Maternal Manganese Restriction Increases Susceptibility to High-Fat Diet-Induced Dyslipidemia and Altered Adipose Function in WNIN Male Rat Offspring - Ganeshan, Manisha (Hindawi Publishing Corporation, 2011)
Growth in utero is largely a reflection of nutrient and oxygen supply to the foetus. We studied the effects of Mn restriction per se, maternal Mn restriction, and postnatal high-fat feeding in modulating body composition, lipid metabolism and adipocyte function in Wistar/NIN (WNIN) rat offspring. Female weanling, WNIN rats received ad libitum for 4 months, a control or Mn-restricted diet and were mated with control males. Some restricted mothers were rehabilitated with control diet from conception (MnRC) or parturition (MnRP), and their offspring were raised on control diet. Some restricted offspring were weaned onto control diet (MnRW), while others continued on restricted diet throughout (MnR). A set of offspring from each group was fed high-fat diet from 9 months onwards. Body composition, adipocytes function, and lipid metabolism were monitored in male rat offspring at regular intervals. Maternal manganese restriction increased the susceptibility of the offspring to high-fat-induced adiposity, dyslipidaemia, and a proinflammatory state but did not affect their glycemic or insulin status.